(untitled) (Journal of the College of Basic Education, 2022)
The policy of al-Nasir li-Din Allah (575-623 AH / 1179-1226 AD) was aimed at directing matters by himself so that nothing of the affairs of the people would be hidden from him and he would not miss a matter of what was happening in his country and other countries of Islam. And those close to him who read him the news of the country and the people inside and outside Iraq. Likewise, the Caliph Al-Nasir for the Religion of God assigned his senior and loyal kings to him some political and military functions in the countries of great prestige. I grew up, in addition to asking them not to underestimate any news, no matter how big or small, about the affairs of the state and the people. .